2011
DOI: 10.1155/2011/762983
|View full text |Cite
|
Sign up to set email alerts
|

Joining Forces: Collaborating Internationally to Deliver High‐Quality, Online Postgraduate Education in Pain Management

Abstract: The effective management of pain is a complex and costly global issue, requiring a range of innovative educational strategies to enable culturally appropriate and high-quality health care provision. In response to this issue, the Pain Management Research Institute at the University of Sydney (Sydney, Australia) has established several strategic alliances with other overseas universities to deliver online postgraduate education in pain management. The present article discusses the rationale for joining forces, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
(17 reference statements)
1
6
0
Order By: Relevance
“…In closing, defining pain stakeholders' main concerns, the present study has also helped define the aspects of pain assessment, management and communication that would need to be included in the undergraduate curriculum to improve patient care and better prepare medical professionals to deal with one of the most common presenting symptoms they will encounter during their career. Answering the call for innovative education technologies to tackle the global challenge of pain management education (39), the next step of the research project has been to embed the identified themes in the design of an e-tool using virtual patient cases for medical undergraduate training, called the Pain Education e-Tool. It is a flexible, web-based program that may fit into crowded curricula because different parts of the cases and resources about pain could be referred to either by educators or by students on their own during their training (40).…”
Section: Discussionmentioning
confidence: 99%
“…In closing, defining pain stakeholders' main concerns, the present study has also helped define the aspects of pain assessment, management and communication that would need to be included in the undergraduate curriculum to improve patient care and better prepare medical professionals to deal with one of the most common presenting symptoms they will encounter during their career. Answering the call for innovative education technologies to tackle the global challenge of pain management education (39), the next step of the research project has been to embed the identified themes in the design of an e-tool using virtual patient cases for medical undergraduate training, called the Pain Education e-Tool. It is a flexible, web-based program that may fit into crowded curricula because different parts of the cases and resources about pain could be referred to either by educators or by students on their own during their training (40).…”
Section: Discussionmentioning
confidence: 99%
“…This applies to the intra-organizational dynamics specifically: the concrete process of selection, management and evaluation, and implementation over time. A handful of studies refer to some steps in passing, but not in a consistent or systematic way (e.g., Devonshire and Siddall, 2011; Marginson, 2015). Other studies do offer some insights into the process of partner selection and maintenance.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…30 Recognising the global context of pain management, competition for students and the challenges of institutional fee structures and the impact on viability, they have developed a range of strategic alliances with overseas institutions. In their paper they describe some of the processes of internationalising their Master's programme and the benefits, challenges and opportunities afforded by these alliances.…”
Section: Innovations In Educational Deliverymentioning
confidence: 99%
“…An exemplar of innovations in the delivery of learning that moves beyond countries is the Pain Management Research Institute at the University of Sydney (Sydney, Australia), which provides online postgraduate pain education and has done so since 1999. 30 Recognising the global context of pain management, competition for students and the challenges of institutional fee structures and the impact on viability, they have developed a range of strategic alliances with overseas institutions. In their paper they describe some of the processes of internationalising their Master's programme and the benefits, challenges and opportunities afforded by these alliances.…”
Section: Innovations In Educational Deliverymentioning
confidence: 99%